Bird remains of Medieval and Post-Medieval coastal sites at the Southern Baltic Sea, Poland. Acta zoologica cracoviensia, 45 (special issue - Daniel Makowiecki; Anne Birgitte Gotfredsen (2002)
Abstract. Rescue excavations in Gdañsk and Koobrzeg starting in the early 1990’s pro-vided new hand collected bird remains. The present paper deals with the results of bird re-mains analyses of three sites from Gdañsk (12th-18th century) and one site from Koobrzeg (10th-12th century). The most frequent bird species was domestic fowl, fol-lowed by goose, and ducks both in Gdañsk and Koobrzeg. The list of wild species con-tains White-tailed Eagle, Crane and Capercaillie most frequently. Introduced species are documented from Gdañsk in the form of one bone of peafowl and several turkey remains. The Gdañsk material exhibits a decrease in the relative frequency of domestic fowl and an increase in the relative frequency of goose over time, reflecting a gradual increase in goose breeding starting in Late Medieval time. A metric analyses showed a general in-crease in body size of domestic fowl over time.